Perkembangan Penggunaan Alat Bukti Dalam Pembuktian Tindak Pidana Dewasa Ini - Annisa, Yulia Dwi; , Hartanto S.H., M.Hum; , Muchamad Iksan S.H.,M.H (2016)
This research aims to (1) determine the development of regulation of evidence in criminal procedural law in Indonesia (2) knowing the practice of evidence related to the development of a variety of evidence in criminal procedure in the State Court of Surakarta. The research is descriptive using empirical juridical approach. The data obtained through research on the the State Court of Surakarta. Data were collected through library research and interviews. Technical analysis of the data of this study is qualitative data analysis using inductive method. The results shows that: (1) Developments regulation evidence in criminal procedural law in Indonesia is influenced by factors: science and technology; crime and modus operandi; and society. (2) The practice of evidence related to the development of a variety of evidence in criminal procedure in the State Court of Surakarta, on the decision of District Court of Surakarta, No.488/Pid.B/2009/PN.Ska related to corruption case with, No 18/Pid.Sus/2015/PN.Ska in the case of Narcotics, and No. 7/Pid.Sus/2011/PN. Ska about a terrorist is evidence witness testimony, expert testimony, letters, instructions, information from the defendant and the evidence addition is electronic document.